Analisis penulisan assesment dan plan pada catatan perkembangan pasien terintegrasi terhadap fraktur femur di rumah sakit X Padang - Azzahra, Rafifah; Nasif , Hansen; Sari , Yelly Oktavia (Journal of Pharmaceutical and Sciences, 2023)
Integrated Patient Progress Notes (IPPNs) is an interprofessional documentation of integrated patient development in the form of patient medical records that serves to improve the quality of interprofessional communication in hospitals. Documentation in the form of a complete IPPNs and the accuracy of writing assessments and plans will help establish smooth collaboration between health workers so that good results can be achieved in healing patients. Fracture is a condition of discontinuity of bone structure caused by trauma or pathological conditions. Femur fracture cases are the most common cases and have a high risk if adequate management is not carried out. This study aims to analyze the accuracy of writing assessment and plan on the Pharmacist's IPPNs for femur fractures in Padang X Hospital. This research is a descriptive qualitative study with prospective data collection from purposive sampling. The results of this study showed that there was no assessment on the Pharmacist's IPPNs (0%) which was written correctly from the 39 Pharmacist's IPPNs analyzed and there was no plan on the Pharmacist's IPPNs (0%) which was written correctly from the 39 Pharmacist's IPPNs analyzed. This study shows that there is no accuracy of pharmacists in writing assessments and plans on IPPNs.